Objects of culture : ethnology and ethnographic museums in Imperial Germany - Penny, H. Glenn (University of North Carolina Press, 2002)
A study which explores the appeal of ethnology in Imperial Germany and analyzes the motivations of the scientists who created the ethnographic museums.